A NOVEL FRACTIONAL STUDY ON FREE CONVECTION FLOW OF BRINKMANN HYBRID NANOFLUID OVER AN INCLINED PLATE - Nisa, Zaib Un; Shafique, Ahmad; Nazar, Mudassar; Asjad, Muhammad Imran; Mahmoud, Khaled H.; Alsubai, Abdullah S. A.; İnç, Mustafa (Vinca Inst Nuclear Sci, 2022)
In this paper a free convection unsteady Brinkmann hybrid nanofluids including two or more nanoadditives to the host liquid is investigated. The physical flow phenomena are illustrated using PDE and thermophysical nanoparticle properties, and this paper addresses the Brinkmann fractional fluid along with chemical reaction and heat generation with ramped conditions over an inclined vertical plate. The heat and molecular fluxes are generalized using the novel fractional derivative. The present flow model are solved semi-analytically using the Laplace transform. The effects of different parameters specially fractional parameter are deliberated and plotted graphically. The acquired results reveal that fractional parameters have dual behavior in velocity profiles and temperature profile. Velocity and temperature are also compared to previous studies. Compared to the other fractional derivatives results, field variables and proposed hybrid fractional derivatives showed a more decaying trend.
Keywords: Brinkmann fluid; hybrid nanofluid; heat generation; chemical reaction; CPC fractional derivative